2023
DOI: 10.1088/1742-5468/acb5ef
|View full text |Cite
|
Sign up to set email alerts
|

Link stability analysis of temporal international fertilizer trade networks

Abstract: Fertilizer availability is crucial for global food security, and international fertilizer trade plays a vital role in reallocating fertilizers across multiple economies. However, the stability of international fertilizer trade relationships between economies has not been studied. Using 29 year records of the global fertilizer trade from 1990 to 2018, we construct three temporal networks linked to three primary nutrients (nitrogen N, phosphorus P2O5, and potash K2O). After introducing the link stability indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…As mentioned above, the platelet membrane (PM) was selected as an optimal coating membrane candidate due to its inherent affinity for vulnerable plaques and its natural presence in atherosclerotic lesions (Figure 2B). 26,27 To prepare PM/Fe 3 O 4 @PLGA, Fe 3 O 4 -loaded PLGA nanoparticles (Fe 3 O 4 @PLGA) were initially synthesized, followed by coating the Fe 3 O 4 @PLGA with the PM using an extrusion method (Figure 2A). Dynamic light scattering (DLS) analysis revealed that the diameter of the nanoparticles increased from approximately 244.13 to 280.33 nm after the PM coating step, corresponding to the thickness of the bilayer membrane (Figure 2C).…”
Section: Syntheses and Characteristics Of The Platelet-coated Fe 3 O ...mentioning
confidence: 99%
“…As mentioned above, the platelet membrane (PM) was selected as an optimal coating membrane candidate due to its inherent affinity for vulnerable plaques and its natural presence in atherosclerotic lesions (Figure 2B). 26,27 To prepare PM/Fe 3 O 4 @PLGA, Fe 3 O 4 -loaded PLGA nanoparticles (Fe 3 O 4 @PLGA) were initially synthesized, followed by coating the Fe 3 O 4 @PLGA with the PM using an extrusion method (Figure 2A). Dynamic light scattering (DLS) analysis revealed that the diameter of the nanoparticles increased from approximately 244.13 to 280.33 nm after the PM coating step, corresponding to the thickness of the bilayer membrane (Figure 2C).…”
Section: Syntheses and Characteristics Of The Platelet-coated Fe 3 O ...mentioning
confidence: 99%